In silico, ADMET and Docking Analysis for the Compounds of Chloroform Extract of Tinospora cardifolia (Wild.) Identified by GC-MS and Spectral Analysis for Antidiabetic and Anti-Inflammatory Activity - Senthil Kumar, D.; Karthikeyan, D.; Roy, Biswabara (Asian Journal of Chemistry, 2022)
The present study was aimed to phytochemical and GC-MS analysis for chloroform extract of Tinospora cardifolia. The structure of the compounds was further confirmed by UV-spectroscopy and FTIR study. The in silico study like molecular, physico-chemical and drug likeliness property was carried out by computational approaches for the identified molecules. Further toxicity potential and pharmacokinetic profile were also determined. The study was carried out using OSIRIS data warrior and Swiss ADME tools. The docking analysis was carried out for the antidiabetic and anti-inflammatory profiles. The compounds were targeted for α-glucosidase, peroxisome proliferator-activated receptor, glucose transporter-1, cyclo-oxygenase-1 & 2 inhibitions. There were around 12 compounds identified by GC-MS analysis. All the compounds exhibited moderate to good drug likeliness and pharmacokinetic potentials. The molecules showed a good bioactivity score against enzyme receptors. The ADMET prediction showed PGP and CYP-inhibitory effects with the least toxic profile. The docking analysis showed strong binding affinity of [1S-(1α,3aα,4α,6aα)]-1H,3H-furo[3,4-c]furan tetrahydrophenyl (molecule-7) on targeted proteins under investigation.